Two-phase evaporative battery thermal management technology for EVs/HEVs: theory and control - Rahman, Mohammed Ataur; Hawlader, Mohammad Nurul Amin; Khalid, Helmi (Springer New York LLC, 2017)
Electrical vehicle needs to draw power from battery for acceleration. It needs to draw high current for speeding up to 130 km/h on 0% gradient and 40 km/h on 5-10% gradient. Battery generates powerful electrical currents to meet the power demands of EV, causing significant warming of the Li-ion cells. The battery operating temperature of 40ºC and above, the battery life span is reduced. The rationale of this study is to develop a fuzzy controlled evaporative battery cooling thermal management system (EC-BThMS) to control the battery temperature in the range of 20ºC - 40ºC. The main objective of the is to develop evaporative cooling battery thermal management system to control the battery temperature in the range of 20ºC – 40ºC both in charging/discharging process and make the system more energy efficient. The proposed system has been developed with estimating the total cooling loads and thermal behavior of the battery cells.A fuzzy controlling system has been introduced with the EC-BThMS to control the electro-compressor and the expansion valve based on the response of battery temperature sensors.The battery temperature profile has been studied in with an EV traveling speed of 60km/h on 0% gradient and 40 km/h on 5% gradient. While, experiment has been conducted on Sepang F1, Malaysia International Formula1 (F1) circuit traveling speed of 130km/h on 420m of 0% gradient in straight track. The maximum battery temperature was recorded 360C for the car travelling on 5% gradient and 390C on Sepang F1 circuit. Comparison has been made on the performance of EC-BThMS with air cooling battery thermal management system (AC-BThMS) by using same car. Result shows that EC-BThMS can save 17.69% more energy than AC-BThM 1 and 23% than with AC- BThMS 2.